Lactobacillus helveticus R0052 and Bifidobacterium longum R0175 Supplementation: An Exploratory, Randomized, Placebo-Controlled Trial of Endocannabinoid and Inflammatory Responses in Female Dancers - Jakub Wiącek; Karolina Skonieczna-Żydecka; Igor Łoniewski; Chariklia K. Deli; Ioannis G. Fatouros; Athanasios Z. Jamurtas; Dominika Moszczyńska; Joanna Karolkiewicz (Microorganisms)
The anandamide (AEA) and lipopolysaccharide (LPS) interaction is gaining attention, but evidence on the influence of probiotics on endocannabinoid system (ECS) biomarkers remains limited. This study (NCT05567653) investigated the effects of 12-week supplementation with Lactobacillus helveticus R0052 and Bifidobacterium longum R0175 on AEA (main outcome) and inflammatory biomarkers in female dancers. Fifteen participants (5 probiotic, 10 placebo) were included in the final analysis. Serum levels of AEA, LPS, and cytokines (tumor necrosis factor-alpha—TNF-α, interleukin-1 beta—IL-1β, and interleukin-10—IL-10) were measured using an ELISA (enzyme-linked immunosorbent assay), and the psychological stress responses were evaluated using the Mini-COPE questionnaire. At the baseline, a correlation between AEA and LPS was observed (Spearman’s r = 0.9677, p < 0.05). After 12 weeks, no statistically significant differences in the AEA, LPS, cytokine levels, or stress-coping strategies were observed between the probiotic and placebo groups (LPS–probiotic: +3.48 EU/L, p = 0.9361; placebo: +56.98 EU/L, p = 0.0694; AEA–probiotic: −1.11 ng/mL, p = 0.9538; placebo: +14.08 ng/mL, p = 0.4749). The direction of change may indicate a trend toward increased inflammation in the absence of probiotics, consistent with patterns described in previous literature. However, these results should be viewed as hypothesis generating and warrant confirmation in larger trials.